2012
DOI: 10.1242/jcs.110460
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinks in the cell wall of budding yeast control morphogenesis at the mother–bud neck

Abstract: SummaryPrevious work has shown that, in cla4D cells of budding yeast, where septin ring organization is compromised, the chitin ring at the mother-daughter neck becomes essential for prevention of neck widening and for cytokinesis. Here, we show that it is not the chitin ring per se, but its linkage to b(1-3)glucan that is required for control of neck growth. When in a cla4D background, crh1D crh2D mutants, in which the chitin ring is not connected to b(1-3)glucan, grew very slowly and showed wide and growing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…2B) shows the typical b-jelly roll arrangement that is common in the GH16 family [29][30][31]. A comparison of the model with the bacterial template indicates that there is an extra loop (residues [22][23][24][25][26][27][28][29][30][31][32][33][34][35] that is located in the active site and not present in the Crh1 model ( Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2B) shows the typical b-jelly roll arrangement that is common in the GH16 family [29][30][31]. A comparison of the model with the bacterial template indicates that there is an extra loop (residues [22][23][24][25][26][27][28][29][30][31][32][33][34][35] that is located in the active site and not present in the Crh1 model ( Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously demonstrated that both Crh1 and Crh2 are responsible for the cross‐linking between chitin and glucan at the yeast cell wall in vivo . Moreover, these cross‐links are essential for the control of yeast morphogenesis at the mother–bud neck . These enzymes act as transglycosylases incorporating β‐1,3‐linked, β‐1,6‐linked and chitooligosaccharides into the cell wall as chitin acceptors .…”
Section: Discussionmentioning
confidence: 99%
“…These modifications were observed along with a diminution of the ␤-1,3-glucan content and an increase in the chitin content. Studies by Cabib and coworkers have shown the importance of chitin and ␤-1,3-glucans during the cell division of yeasts (38)(39)(40). Their work focused on the remodeling of the cell wall during cell division, and particularly on the neck at the mother-bud interface.…”
Section: Discussionmentioning
confidence: 99%
“…The large diameter of the necks of these buds signifies that the size of the cytokinetic ring of septins and contractile proteins is not fixed, reminiscent of consequences of deletion of the bud neck kinase, Cla4, from haploid cells (59).…”
Section: Discussionmentioning
confidence: 99%